SMARCA4-deficient Sinonasal Carcinoma: A Series of 10 Cases Expanding the Genetic Spectrum of SWI/SNF-driven Sinonasal Malignancies - Agaimy, Abbas; Jain, Deepali; Uddin, Nasir; Rooper, Lisa M.; Bishop, Justin A. (American Journal of Surgical Pathology, 2020)
The molecular pathogenesis of poorly differentiated sinonasal carcinoma received significant attention in recent years. As a consequence, several unclassified carcinomas in the morphologic spectrum of sinonasal undifferentiated carcinoma have been reclassified as distinctive genetically defined variants or entities. Among the latter are NUT-rearranged carcinoma and SMARCB1-deficient carcinomas. In this study, we further characterize a rare variant of sinonasal undifferentiated carcinoma-like tumors characterized by inactivation of the SWItch/Sucrose Nonfermentable chromatin remodeler SMARCA4 (BRG1) detectable by immunohistochemistry. Patients were 7 males and 3 females aged 20 to 67 years (median, 44). Tumors originated in the nasal cavity (6), nose and sinuses (2), or at unspecified site (2). Six tumors were initially misdiagnosed as small cell neuroendocrine carcinoma (SCNEC) or large cell neuroendocrine carcinoma (LCNEC). Histologically, the tumors were composed of small basaloid (3 cases) or large epithelioid (7) cells disposed into nests and solid sheets with extensive areas of necrosis. No glands or other differentiating features were noted. Abortive rosettes were seen in 1 case. Immunohistochemistry showed consistent expression of pankeratin and absence of CK5, p63, p16, and NUT in all tumors tested. Other tested markers were variably positive: CK7 (2/6), synaptophysin (9/10; mostly focal and weak), chromogranin-A (4/10; focal), and CD56 (3/5; focal). All tumors showed total loss of SMARCA4 and retained expression of SMARCB1/INI1. Co-loss of SMARCA2 was seen in 1 of 8 cases. Limited data were available on treatment and follow-up. Two patients received surgery (1 also radiotherapy) and 3 received chemotherapy. Metastases (cervical nodes, liver, bone, and lung/mediastinal) were detected in 3 patients; 2 were alive under palliative chemotherapy at 8 and 9 months while 1 died of progressive lung disease at 7 months. Three patients (1 with brain invasion) died soon after diagnosis (1 to 3 mo). In total, 4 of 6 patients (66%) with follow-up died of disease (median, 3 mo). This series characterizes SMARCA4-deficient sinonasal carcinoma as a genetically distinct aggressive entity in the spectrum of undifferentiated sinonasal carcinomas. These variants add to the spectrum of SWItch/Sucrose Nonfermentable-deficient sinonasal carcinomas, at the same time expanding the topographic distribution of SMARCA4-related malignancies.
CRIS-Team Scopus Importer:2020-02-04
Keywords: large cell; neuroendocrine carcinoma; NUT midline carcinoma; sinonasal; small cell carcinoma; SMARCA4; SMARCB1; SNUC; SWI/SNF complex